2011
DOI: 10.1007/978-1-4419-9586-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Equilibrium Models for Generation Capacity Expansion

Abstract: Capacity expansion models in the power sector were among the first applications of operations research to the industry. We introduce stochastic equilibrium versions of these models that we believe provide a relevant context for looking at the current very risky market where the power industry invests and operates. We then look at the insertion of risk related investment practices that developed with the new environment and may not be easy to accommodate in an optimization context. Specifically we consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…An alternative is to assume complete financial markets, such that investors can trade all types of risk (e.g., there exist Arrow-Debreu securities for all future scenarios). This reduces the complexity of the problem and, like the assumption of perfect competition in energy markets, can make risk-averse planning problems much more tractable (see, e.g., Ehrenmann and Smeers, 2011b). It may, however result in an overestimation of investment levels and in an underestimation of the strategic interactions between market participants, including the need for individual investors to hold diversified portfolios, although it is unclear what the practical implications of the latter would be for aggregate investment levels.…”
Section: The Role Of Financial Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative is to assume complete financial markets, such that investors can trade all types of risk (e.g., there exist Arrow-Debreu securities for all future scenarios). This reduces the complexity of the problem and, like the assumption of perfect competition in energy markets, can make risk-averse planning problems much more tractable (see, e.g., Ehrenmann and Smeers, 2011b). It may, however result in an overestimation of investment levels and in an underestimation of the strategic interactions between market participants, including the need for individual investors to hold diversified portfolios, although it is unclear what the practical implications of the latter would be for aggregate investment levels.…”
Section: The Role Of Financial Marketsmentioning
confidence: 99%
“…As mentioned above, this is an obvious simplification since modeling of financial markets is outside the scope of this work, but it would be even less appropriate to ignore their (beneficial) effects altogether. It has been shown that, given these assumptions, the generation dispatch and generation expansion equilibrium is equivalent to the solution of a risk-adjusted cost minimization problem (Ralph and Smeers, 2010;Ehrenmann and Smeers, 2011b) 5 . This is intuitive -complete financial markets ensure that the worst-case scenario is the worst case for every market participant; perfect competition then restores the market equilibrium to its risk-averse social optimum.…”
Section: Modeling Risk Averse Equilibriamentioning
confidence: 99%
“…The electricity investment model proposed in [11] is of this type and was one of the inspirations for the work presented here. Our paper, or rather the first version of it [26], is cited in work on two-stage capacity equilibria [12] and two-stage hydropower equilibria [25]. It is also cited in [22], which combines a market in financial instruments with a spot electricity market, Downloaded 01/05/16 to 131.111.184.102.…”
Section: Motivation and The Broader Literaturementioning
confidence: 99%
“…. , N) and (12) in statement B of Theorem 7 can be equivalently written as the Nash game that combines (16) (for i = 1, . .…”
Section: A Risky Design Equilibrium Problem Is Equivalent To a Nash Gmentioning
confidence: 99%
“…In many of these studies, bilevel or trilevel problems are cast as mathematical programs with equilibrium constraints (MPECs) or equilibrium problems with equilibrium constraints (EPECs) and are solved by equivalent single-level reformulations of the multilevel problem. In [9], the author shows that a hierarchical bilevel model formulated as an MPEC and a simultaneous model formulated as an MCP lead to the same results in a perfectly competitive market structure and under some mild conditions; see also, e.g., [13,17] for similar results in comparable settings. Hence, in this paper, we resort our attention to MCP formulations.…”
Section: Introductionmentioning
confidence: 90%